Burundi : Poverty Reduction Strategy Paper; Annual Progress Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report, 2009)
This Joint Staff Advisory Note focuses on the Poverty Reduction Strategy Paper-Annual Progress Report (APR) for Burundi. Slow implementation of structural reforms, a sharp decline in coffee production, and the unstable security situation are largely responsible for lower-than-expected economic growth. Poor weather conditions and rising international petroleum and food prices are the main factors behind the faster-than-expected increase in domestic consumer prices. The APR also discusses the issue of regional economic integration, which is one of the elements that will shape medium-term economic developments in Burundi.